TICACOS international: A multi-center, randomized, prospective controlled study comparing tight calorie control versus Liberal calorie administration study. Issue 2 (February 2021) - Singer, P.; De Waele, E.; Sanchez, C.; Ruiz Santana, S.; Montejo, J.C.; Laterre, P.F.; Soroksky, A.; Moscovici, E.; Kagan, I.
Summary: Since the first TICACOS study, 3 additional studies have been published comparing a medical nutrition therapy guided by indirect calorimetry to a regimen prescribed on the basis of predictive equations. A recent guidelines document included a meta-analysis including these 4 papers and found a trend for improvement (OR 0.98–1.48) in favor of medical nutrition therapy guided by indirect calorimetry in terms of survival. The aim of our study was to perform a multicenter prospective, randomized, controlled non blinded study in critically patients to assess the added value for measuring daily resting energy expenditure as a guide for nutritional support. The primary objective was to decrease infectious rate of these critically ill patients. Material and methods: This phase III, multi-center, randomized, controlled non blinded study was planned to include 580 newly-admitted, adult ventilated ICU patients that were planned to stay more than 48 h in the ICU departments. The nutritional support was aimed to meet 80–100% of energy requirement measured by indirect calorimetry. The calorie needs were determined by IC in the Study group and by an equation (20-25 kcal/kg ideal body weight/day) in the Control Group. The ICU staff was trained to strive to supply 80–100% of a patient's energy requirements through artificial nutrition, preferably enteral feeding. Primary endpoint was infection rate and secondary endpoints included other morbidities and mortality during ICU, at 90 and 180 days. Comparison between the study and the control group was performed using T test for equality of means (independent samples test). Correlations were performed using the Pearson correlation test. A p level of 0.05 or below was considered as significant. Cross tabs procedure used Chi-square test for testing differences in complication rates, length of stay and length of ventilation. Correlations between energy balances and complications was also be tested using one way analysis as well as ANOVA analysis between groups and within groups. Kaplan Meir curves assessed the proportion of surviving patients in the 2 groups. Results: Seven centers with a calorimeter available participated to the study. Due to slow inclusion rate, the study was stopped after 6 years and after inclusion of 417 patients only. From the 417 intended to treat patients, 339 followed the protocol. There was no differences between control and study groups in terms of age, sex BMI, SOFA (7.1 ± 3.1 vs 7.4 ± 3.3) and APACHE II scores (22.4 ± 7.9 vs 22.2 ± 7.4). The rate of infection (40 vs 31), including pneumonia rate, need for surgery, dialysis requirement, length of ventilation, ICU length of stay, and hospital length of stay were not different between groups. Mortality (30 in the control vs 21 in the study group) was not significantly different between groups. The decreased mortality observed in the study group when added to previous studies may have a positive effect on the meta-analysis previously published. Conclusion: Tight Calorie Control guided by indirect calorimetry decreased the rate of infection and mortality but not significantly. This may be explained by the not relatively small sample size. There results together with the previous 4 prospective randomized studies, may improve the results of the meta-analysis exploring the effects of IC guided nutrition on mortality.